Innovation in Startup for Sustainability : Study in Jakarta - Indrajaya, Sonny; Kurniawan , Deden; Setyaningrum, Retno Purwani (Adpebi Science Series, 2023)
Business actors start intense competition and make more effective market penetration breakthroughs in order to survive. It is important to optimize the marketing system of startup companies. Competition between the world of business and industry in the 19th pandemic era became interesting because of the rapid development of startup businesses in Jakarta. Innovation and social media that can increase business sustainability. The research was conducted for 6 months. The sample was 50 startup companies and taken via Google or online in Jakarta. The analysis tool uses Wrap PLS. This research aims to provide an overview of innovation and social media to support the sustainability of startup businesses. In this research, the influence of innovation and social media on business continuity and startup companies can be seen.